Skill needs in enterprises: CVTS results - Behringer, Friederike [Verfasser] (My University, 2009)
"The European Survey of Continuing Vocational Training in enterprises (CVTS) is the only data source that provides detailed internationally comparable Data on enterprise provided continuing training. CVTS3 took place in 2006 in the 27 Member States an Norway, relating to training activities and training policies in 2005. CVTS2 covered 25 European countries, the reference period was 1999. Below are findings, based on CVTS2 and CVTS3, on skill needs in enterprises. According to CVTS, enterprises awareness of skill needs is rather low. Further, many enterprises have no procedures to assess future skill needs. The final section suggests some conclusions on the possible role of enterprise surveys like CVTS in the context of Skillsnet." (Autorenreferat, BIBB-Doku)
Keywords: S 1.5.3 Betriebliche Weiterbildung; G 1.2.3.2 Anforderungen & Bedarfe; T 3.4 Befragung; Betriebliche Weiterbildung; Qualifikationsbedarf; Weiterbildungsbedarf; Unternehmen; CVTS; Europa